EFEK DARI KEPEMIMPINAN KARISMATIK DAN BUDAYA ORGANISASI ATAS LOYALITAS ORGANISASI MELALUI KEPUASAN KERJA SEBAGAI MODERASI STUDI DINAS PARIWISATA KABUPATEN DEMAK - Aditya Angger Wibowo (Jurnal Bina Bangsa Ekonomika, 2024)
The study aims to study how organizational culture and charismatic leadership affect employee loyalty and job satisfaction. This study involved non-ASN employees from the Demak Regency Tourism Office. Using the porposive sampling method, 126 employees filled out questionnaires independently to obtain secondary data. After that, the data was processed using SEM AMOS. Confirmatory analysis is used to evaluate the size of endogenous and exogenous constructs. This study shows that charismatic leadership increases job satisfaction. Charismatic leadership increases employee loyalty, organizational culture increases employee loyalty, and job satisfaction decreases employee loyalty